“Ellos y nosotros”. Fronteras sociales en los años del primer peronismo - Rosa Aboy (Nuevo mundo - Mundos Nuevos, 2008)
In Buenos Aires, capital city of Argentina, the demographic pressure of rural migrants, atracted by the process of industrial development, triggered by mid-1940s a major housing deficit. Peronist policies on this subject promoted social and spatial inclusion of the recently arrived. This situation produced a social crisis resulting from the working and the middle classes (mostly descendants of European inmigrants), who distrusted those who had arrived from the poorest provinces in Argentina, and their will to live away from them. During the Post War years, these conflicts confronted the urban middle class with the ones called “cabecitas negras”. This article explores the problematic relationship between both groups, developping an analysis at a micro-historiographic level, in an attempot to get closer to the study of the social conflict between new and old urban residents. Based upon oral testimonies, it focuses on the construction of social boundaries and segregation mechanisms in terms of class, race and culture.